The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/mnras/stac2514
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-scale radio surveys of star formation and feedback in Triangulum Galaxy M 33: VLA observations

Abstract: Studying the interplay between massive star formation and the interstellar medium (ISM) is paramount to understand the evolution of galaxies. Radio continuum (RC) emission serves as an extinction-free tracer of both massive star formation and the energetic components of the ISM. We present a multiband RC survey of the Local Group galaxy M 33 down to ≃30 pc linear resolution observed with the Karl G. Jansky Very Large Array (VLA). We calibrate the star formation rate surface density and investigate the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…This is expected since most Σ SFR upper limits are distributed near the low Σ mol end of the mKS relation, without which the average Σ SFR value is biased high at low Σ mol , and thus the power-law slope is biased low. Beside the treatments of data censoring, the handling of measurement uncertainties and choice of regression methods could also affect the fit result (e.g., de los Reyes & Kennicutt 2019; Tabatabaei et al 2022).…”
Section: Appendix a Data Productsmentioning
confidence: 99%
“…This is expected since most Σ SFR upper limits are distributed near the low Σ mol end of the mKS relation, without which the average Σ SFR value is biased high at low Σ mol , and thus the power-law slope is biased low. Beside the treatments of data censoring, the handling of measurement uncertainties and choice of regression methods could also affect the fit result (e.g., de los Reyes & Kennicutt 2019; Tabatabaei et al 2022).…”
Section: Appendix a Data Productsmentioning
confidence: 99%
“…At a distance of 817 kpc (Freedman et al 2001), M33 is the second closest star-forming spiral galaxy. It lies at medium inclination (i = 52°; Kam et al 2015) and has been well-observed across the electromagnetic spectrum (radio: Israel & van der Kruit 1974;Tabatabaei et al 2022; optical/UV: Williams et al 2021;γ-ray: Xi et al 2020). Previous X-ray surveys have localized point sources with high accuracy using the Chandra X-ray Observatory (Tüllmann et al 2011, T11 hereafter), as well as with wide area coverage and several epochs observed by XMM-Newton (Misanovic et al 2006;Williams et al 2015, M06 and W15 hereafter).…”
Section: Introductionmentioning
confidence: 94%
“…However, the radio continuum (RC) emission from galaxies is not purely due to synchrotron radiation. Particularly in star-forming regions, the RC emission can be due to the free-free radiation of thermal electrons by about 50% (30%) or even higher at 6 GHz (1 GHz, Tabatabaei et al 2013Tabatabaei et al , 2022. A correction is hence needed to map the synchrotron radiation and to study the thermal and non-thermal processes in galaxies.…”
Section: Ism/igm Evolution With Jwst and Skamentioning
confidence: 99%
“…The free-free and synchrotron components of the RC surface brightness of the mainsequence galaxies such as M51, NGC6946, and M33 are simulated back to cosmic noon (z ∼ 3) taking into account the SKA1-MID band 2 angular resolution of 0.6 arcsec (corresponding to maximum sensitivity at 1.4 GHz in phase 1) and adding the sky levels of WT, DT, and UDT surveys as background noise (Ghasemi-Nodehi et al 2022). These simulations make use of the available free-free emission maps of M51, NGC6946, and M33 obtained using de-reddened Hα emission maps (Tabatabaei et al 2013(Tabatabaei et al , 2022 tracing the thermal processes in the ionized ISM as well as their pure synchrotron maps tracing the non-thermal processes. Both processes can be detected in M51 and NGC6946 analogs back to cosmic noon, but they are hardly detected in low mass M33 analogs at z > 0.5 by the proposed SKA1 surveys.…”
Section: Thermal and Non-thermal Processes Back To Cosmic Noonmentioning
confidence: 99%